Evidence-Based Electroconvulsive Therapy for Major Depression Disorder - Zahra D Khan; Carla Raymondalexas Marchira; Patricia Wulandari (HM Publisher, 2020)
Electroconvulsive Therapy (ECT) is a treatment that steals medical attention and the public. Memory disturbance after ECT is a special consideration for the Food and Drugs Administration (FDA) of the United States to classify ECT, whether it belongs to class III (high risk). Psychiatrists or anesthesiologists (who are experienced with ECT) tend to change this classification, while neurologists, psychologists, biostatistics experts, and public representatives agree to maintain ECT status in class III. Contrary to unexpected effects, ECT can induce a transition in severe melancholic patients and suicide to normal functioning humans, after other treatments have failed. With the aim of balancing effectiveness and safety, this paper provides modern evidence of the benefits and risks of ECT.